Urban sprawl processes joining cellular automata, GIS and remote sensing data: simulation of details un-authorized development - Mohd. Noor, Norzailawati; Hashim, Mazlan (2010)
The paper explores a framework combining remote sensing and GIS-cellular automata concepts aimed at improving the modeling of un-authorized development. We highlighted that this integration will lead to new levels of understanding of how urban areas grow and change. Further, we describe an unauthorized development for the city of Kuantan in Malaysia, in which urban cellular automata (CA.) concepts is used. The model for Kuantan city was calibrated and tested with the aid of measured time-series data on land uses, through a set of statistical analysis. The fifteen-year simulation until 2015 was run. The simulations applied nearly achieve a high level of detail, confirming the effectiveness of the proposed model with some questions of future research are finally put forward to help strengthen the potential of the proposed framework, especially regarding the further exploration of urban dynamics at high level geographic states.